Penerapan Asesmen Kinerja Untuk Mengukur Kemampuan Komunikasi Matematis Dan Kemandirian Belajar Siswa SMK - Gumiarti, Hinda (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2014)
This research is intended to study the improvement of mathematical communication ability problems and students’ learning activity independency thorough learning activity with performance assessment and also to gain students activity learning description in learning mathematics. The methodology of this research is the alloyment of qualitative data embedded into quantitative. The population of this research are 14 classes of XI yearstudents of SMK Negeri 1 Cianjur. And the sample are the XI year students of RPL 1 as experimental class and XI year students of TKJ 1 as control one. Its instrument is questions about mathematical communication ability and questionnaire of students’ learning independency scale, activity observation sheet, and students interview sheet. The result of this research is 1)The improvement of students mathematical communication ability which use the performance assessment better than those who learn the material with conventional one; 2) There is some improvement of mathematical communication ability with performance assessment; 3)The students are actively involved in learning process with performance assessment